The effect of polarized training on the athletic performance of male and female cross-country skiers during the general preparation period - Kim. T. H.; Han, J. K.; Lee, J. Y.; Choi, Y. C. (healthcare, 2021)
This study aimed to analyze the effect of 12 weeks of polarized training on body composition, cardiorespiratory function, and upper-body power of male and female cross-country skiers during the general preparation period. A total of 16 national cross-country skiers (8 male and 8 female; 8 national cross-country skiers and 8 national biathlon athletes) participated. Polarization training was conducted for 12 weeks from May to July in 2019 during the general preparation period for cross-country skiers. The low-weight, high-repetition method was used for strength training. The effect of the polarized training on body composition, maximum oxygen intake (VO2max), respiratory exchange rate, all-out time, and ski ergometer exercise time was assessed. There was no change in weight, BMI, and muscle mass in male and female cross-country skiers following the 12 weeks of polarized training (p > 0.05). Male body fat percentage (pre 18.1%, post 12.7%) and female body fat percentage (pre 29.1%, post 21.4%) showed a significant decrease (p < 0.05). After training, VO2max increased by 7.72% in male athletes (pre 71.05 mL/kg/min, post 77.0 mL/kg/min) and 6.32% in female athletes (pre 60.26 mL/kg/min, post 64.33 mL/kg/min). Treadmill exercise time increased by 5.39% for male athletes (pre 1038 s, post 1064 s) and 2.23% for female athletes (pre 855 s, post 874 s). However, there was no significant difference between male and female athletes (p > 0.05). The 50% recovery time from the maximum heart rate to the target heart rate decreased by 64.52% in males (pre 168.8 s, post 102.6 s) and 6.48% in females (pre 135 s, post 129.6 s). Significant differences were found only in male athletes (p < 0.05). The double-pole 500 m exercise duration for the ski ergometer significantly decreased after the training for both sexes (p < 0.05). In this study, the 12 weeks of polarized training improved the body composition and athletic performance of all cross-country skiers. Interestingly, in this study, we confirmed that polarized training had a better effect on cardiorespiratory function in male cross-country skiers than in female cross-country skiers. Conversely, we found that the outcomes of the ski ergometer exercise factors were more effective in female athletes than in male athletes. Therefore, we insist that when applying a polarized training program to athletes, it should be planned in detail by sex, exercise amount, intensity, and type of training.